Upaya Perlindungan Hukum Bagi Para Konsumen Pemegang Aset Kripto di Indonesia - Atmojo, Robertus Nugroho Perwiro; Fuad, Fokky (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This research focuses on analyzing the regulations governing the legal aspects related to crypto assets and their protection. Within this analysis, attention is directed toward the three fundamental pillars of Indonesian law, namely justice, certainty, and expediency. Additionally, this study identifies two pertinent issues. The first pertains to legal regulations concerning the legitimacy of crypto assets. The second involves the form of legal protection provided to holders of crypto assets in general, as well as to those who possess NFT and SFT-based crypto assets specifically. The findings of this study outline several strategies aimed at enhancing regulations governing the trade, use, and circulation of crypto assets in Indonesia. These strategies encompass protective measures that guarantee the quality of block chain technology system performance, ensure value preservation in crypto asset trading, facilitate dispute resolution in crypto asset trading, and endeavor to safeguard Intellectual Property Rights (IPR) in crypto asset trading.